Does Adiponectin Act as an Antiangiogenic Factor in B-Cell Chronic Lymphocytic Leukemia?. (24th June 2009) - Molica, Stefano; Digiesi, Giovanna; Vacca, Angelo; Mirabelli, Rosanna; Todoerti, Katia; Battaglia, Caterina; Morabito, Fortunato; Neri, Antonino; Ribatti, Domenico
Abstract : Angiogenesis is involved in the pathogenesis of B-cell chronic lymphocytic leukemia (CLL), and high microvascular density has been found in CLL to be associated with a poor prognosis. In this study, we assessed serum levels of adiponectin in 69 patients with Binet stage A B-CLL, and these values were retrospectively correlated with bone marrow (BM) microvessel area and serum levels of vascular endothelial growth factor (VEGF), fibroblast growth factor-2 (FGF-2), angiogenin, PECAM-1 (CD31), matrix metalloproteinase-9 (MMP-9), interleukin-8 (IL-8), syndecan-1, and the percentage ofCD 38 + orZAP- 70 + CLL cells. The positive correlation between serum levels of adiponectin and VEGF (P = .03 ) does not translate into an increase of the extent of BM angiogenesis (P = .404 ), FGF-2 (P = .348 ), angiogenin (P = .402 ), and CD31 (P = .248 ) serum concentrations. Accordingly, IL-8 (P = .175 ), syndecan-1 (P = .06 ), and MMP-9 (P = .144 ) circulating levels were not likely to reflect adiponectin concentration. Furthermore, patients with higher levels of adiponectin had a more favorable biological profile as defined by a lower number of bothCD 38 − (r = − 0.294 ;P = .02 ) andZAP- 70 + (r = − 0.285 ;P = .04 ). Finally, we evaluated the presence of adiponectin in B-CLL cells at gene expression level. RMA intensity values for adiponectin gene transcript denote a homogeneous low expression in B-CLL cells, whereas VEGF transcript was highly expressed with a degree of interpatient variability. Overall, these data seem to indicate that adiponectin could be involved as an antiangiogenic factor in B-CLL.